Clinicomicrobiological profile of endophthalmitis: A 10 year experience in a Tertiary Care Center in North India - Gita Satpathy; Niranjan Nayak; Meenakshi Wadhwani; Pradeep Venkwatesh; Atul Kumar; Yograj Sharma; Vishnu Sreenivas (Wolters Kluwer Medknow Publications, 2017)
Purpose: To determine the clinicomicrobiological profile of infectious agents and their antibiotic susceptibility in different type of endophthalmitis. Methods: A retrospective review of clinical and microbiological records from January 2001 to December 2010, was performed in 1110 patients diagnosed with different type of endophthalmitis (postoperative, posttraumatic, endogenous and post keratitis) to record the demographic details, clinical presentations; microbiological agents isolated with their antimicrobial sensitivity pattern. Antimicrobial susceptibility testing for various culture positive isolates (bacterial/fungal) was performed by the disc diffusion technique. Results: Out of the 1110 intra-ocular specimens processed, 384 (34.6%) were positive for bacteria. S epidermidis was the most predominant isolate accounting for 42.7% of all bacteria obtained, followed by Pseudomonas aeruginosa (24.5%). Besides Pseudomonas, Acinetobacter spp. were the next common gram negative bacilli detected (8.3%) followed by Klebsiella, E. coli, Enterobacter and Alkaligenes in 2.6%, 0.8%, 0.8% and 0.5% cases respectively. The predominant fungal species were Aspergillus spp., in 36.1%, followed by Fusarium spp. in 26.4% cases. Overall susceptibility pattern in our study showed that gram positive bacteria were most susceptible to glycopeptides like vancomycin (80-100%) and fluoroquinolones (87-91%). The sensitivity pattern of gram negative organisms like Pseudomonas and Klebsiella towards fluoroquinolones ranged between 61% - 82%. Conclusion: S epidermidis was the most common bacteria isolated in postoperative and posttraumatic endophthalmitis, Pseudomonas aeruginosa was the most common bacterial isolated in posttraumatic endophthalmitisAmongst fungi Aspergillus was the most common organism.